Prevalence of anemia and associated factors in children aged 6-59 months in Pernambuco, Northeastern Brazil - Leal, Luciana Pedrosa; Batista Filho, Malaquias; Lira, Pedro Israel Cabral de; Figueiroa, José Natal; Osório, Mônica Maria (Revista de Saúde Pública, 2011)
OBJECTIVE: To estimate the prevalence of anemia and to identify its associated factors in children aged 6-59 months. METHODS: This was a cross-sectional study on data from the Third Health and Nutrition Survey of the State of Pernambuco, Northeastern Brazil, with a representative sample of 1,403 children from urban and rural areas. Anemia was diagnosed by means of hemoglobin assays. Multivariate analysis was performed though a hierarchical model, using robust-variance Poisson regression to estimate the prevalence ratio as a function of the following variables: biological factors, morbidity, child nutritional state, socioeconomic factors, housing, sanitation and maternal factors. RESULTS: The weighted prevalence of anemia was 32.8% overall: 31.5% in urban areas and 36.6% in rural areas. In urban areas, anemia was significantly associated with maternal education, consumer goods, number of children less than five years old in the home, drinking water treatment, maternal age, maternal anemia and the child's age. In rural areas, only maternal age and the child's age were significantly associated with anemia. CONCLUSIONS: The prevalence of anemia in children in Pernambuco was similar in urban and rural areas. The factors associated with anemia that are presented here should be taken into consideration in planning effective measures for its control.